Global Affairs Canada: an approach to development innovation - and GAC (Global Affairs Canada, 2018)
For Global Affairs Canada, development innovation includes new or improved business models, policy practices, approaches, technologies, behavioral insights or ways of delivering products and services that benefit and empower the poorest and most vulnerable people in developing countries.